Becoming Mobile Readers-Narratives of Zimbabwean Teenagers’ Mobile Reading Experiences - Bachisi, Ivan (Universitas Pendidikan Mandalika, 2023)
This article critically reviews the mobile reading experiences of a group of twenty-three Zimbabwean urban adolescent learners. This paper contends that while mobile reading is a growing mode of literacy development across the world, little is known about the different strategies Zimbabwean adolescent learners have had to employ as they reconfigure and rethink their literacy practices around new reading media like cell phones and tablets. This paper adopts a constructivist approach to trace, document, and analyse the personal narratives of the participants’ mobile reading experiences during their transformational journeys towards becoming active mobile readers. The participants’ voices were captured using task-based evaluative focus group interviews. Through this cooperative collaborative approach, the researcher managed to engage the participants on critical issues surrounding their digital literacy practices, their digital identities, their digital inclusion, and digital exclusion thereof. It was established that the adolescent participants were a digital generation living in a digital age and their reading needs and expectations were ever-growing and ever-changing. The adolescent participants expected their digital reading to be like the rest of their digital lives: quick, uninterrupted, personalised, and smart. Educational practitioners ought not to assume that adolescent learners as digital natives will automatically become successful mobile readers, but rather they should make accommodations for, and teach adolescents the art of digital learning and mobile reading. This paper recommends the scaling up of mobile reading initiatives and research in Zimbabwe so that the mobile reading phenomenon is further demystified.